METODE PARTIAL LEAST SQUARE (PLS) DAN TERAPANNYA (Studi Kasus: Analisis Kepuasan Pelanggan terhadap Layanan PDAM Unit Camming Kab. Bone) - Irwan, Irwan; Adam, Khaeryna (Teknosains: Media Informasi Sains dan Teknologi, 2015)
Water is primer necessity of human. The needs of clean water always increasingly through the time. PDAM or district water supply company as a local company that have duty to distribute clean water for the peoples need to increasing the serve quality for the satisfied of customer. Theaim of this research is to know the influence of PDAM Unit Camming for the satisfied of customer.Method that used to survey the customer satisfied is SERVQUAL method (Service Quality) that have 5 dimension, such as: Tangible, Reliability, Responsiveness, Assurance, and Emphaty. Analysismethod that used is Partial Least Square (PLS). Theresult of this research is how the 5 dimension of SERVQUAL influence the satisfied of PDAM Unit Camming customer. Wecan see the result in R square that get by smartPLS helped. Theresult showed 0,706. Its mean, the 5 dimension of SERVQUAL can explain that 70,6% satisfied of PDAM Unit Camming customer. However, there still have serve quality dimension that need to repair, such as responsiveness and tangible. Thistwo things must be repaired to increasing the serve of PDAM Unit Camming and also can increase the satisfied of customer.